2011
DOI: 10.1177/2151458511430664
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Knee Dislocation Following Septic Arthritis of the Knee

Abstract: This is a report of a case of nontraumatic posterior knee dislocation following septic arthritis in a 59-year-old male with leucopenia secondary to sarcoidosis. After confirmation of the diagnosis with synovial fluid analysis, the patient was taken emergently to the operating room for arthroscopic-assisted irrigation and debridement. Arthroscopy demonstrated intact cruciate ligaments but confirmed the diagnosis of septic arthritis demonstrating purulent synovial fluid. He was discharged after multiple repeat i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…So deterioration of cruciate ligaments is easier after infection in elderly patients. 8 , 9 These assertions explain the dislocation mechanism with a minor trauma in our elderly patient. Our patient similar to the other two cases did not have a major trauma.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…So deterioration of cruciate ligaments is easier after infection in elderly patients. 8 , 9 These assertions explain the dislocation mechanism with a minor trauma in our elderly patient. Our patient similar to the other two cases did not have a major trauma.…”
Section: Discussionmentioning
confidence: 57%
“…Post-arthroscopic infection is previously well defined and discussed in the literature but there has been no report of knee joint dislocation following infection. Bonnaig et al 8 reported a case of non-traumatic posterior knee dislocation following septic arthritis in a 59-year old female with leukopenia secondary to sarcoidosis. This patient had undergone corticosteroid injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Bonnaig et al . [ 5 ] reportof a spontaneous knee dislocation after septic arthritis, the patient’s risk factors such as sarcoidosis and leukopenia made the patient in greater risk of total knee prosthesis infection, therefore, making arthrodesis more favorable in their case. However, when eradication of infection is possible and the patient possesses no risk factors that may increase the risk of prosthesis infection, TKR would be a suitable management option as demonstrated in Oztürkmen et al .…”
Section: Discussionmentioning
confidence: 99%